Adoption of Improved Agricultural Practices by Pepper Growers of Idukki District - Gangadharan K K (Department of Agricultural Extension, College of Agriculture, 1993)
The study on the adoption of improved agricultural practices in pepper was conducted in Idukki district of Kerala with the following objectives: 1) To study the extent of awareness of improved agricultural practices in pepper by pepper growers. 2) To study the extent of knowledge about improved agricultural practices in pepper by pepper growers. 3) To study the attitude of pepper growers towards improved agricultural practices in pepper. 4) To study the extent of adoption of improved agricultural practices in pepper. 5) To study the relationship between the extent of awareness, knowledge, attitude and adoption with the socio- psychological and economic characters of pepper growers; 6) To identify the constraints in adoption of improved agricultural practices in pepper and to suggest solutions to overcome the constraints. A total of 200 pepper growers were selected from 10 krishi bhavans for the study, using stratified two- stage sampling procedure. Data were collected by using a structured interview schedule during the months of June and July 1992. The important findings of the study were the following. A majority of pepper growers in the study area had medium level of awareness of improved agricultural practices in pepper. The independent variables, namely, education, scientific orientation, economic motivation, risk orientation, cosmopoliteness, information source used, social participation, innovativeness, contact with extension agency and market orientation were positively and significantly related with awareness. But age was found negatively and significantly correlated with awareness of improved agricultural practices in pepper. Majority of pepper growers had medium level of knowledge about the improved agricultural practices in pepper. The independent variables, namely, education, scientific orientation, economic motivation, risk orientation, cosmopoliteness, information source used, social participation, innovativeness, contact with extension agency and market orientation were positively and significantly related with knowledge of improved agricultural practices in pepper, whereas age was found negatively and significantly correlated with knowledge. In the case of attitude of pepper growers, majority of pepper growers had a medium level of attitude towards improved agricultural practices in pepper. Education, scientific orientation, economic motivation, risk orientation, cosmopoliteness, information source used, social participation, innovativeness, contact with extension agency and market orientation were positively and significantly related with attitude of pepper growers towards improved agricultural practices in pepper. Age was found negatively and significantly correlated with attitude. A majority of pepper growers in the study area had medium level of adoption of improved agricultural practices in pepper. The independent variables namely, education, scientific orientation, economic motivation, risk orientation, cosmopoliteness, information source used, social participation, innovativeness, contact with extension agency and market orientation were positively and significantly related with adoption of improved agricultural practices in pepper. Age was found negatively and significantly correlated with adoption. Step-wise regression analysis revealed that education was the most important variable in prediction of the extent of awareness, followed by scientific orientation, economic motivation, risk orientation, cosmopoliteness, information source used, innovativeness, contact with extension agency and market orientation. The seven variables jointly explained 65 per cent of variation in extent of awareness of improved agricultural practices in pepper. Education alone contributed 41 per cent of variation in prediction. In the case of knowledge about improved agricultural practices in pepper, education was found as the most important variable in prediction, which alone contributed 50 per cent of variation in the extent of knowledge. The independent variables, namely, education, contact with extension agency, innovativeness, social participation, scientific orientation, risk orientation, information source used and market orientation had jointly explained about 74 per cent of variation in the extent of knowledge about improved agricultural practices in pepper. Scientific orientation was found as the most important variable in prediction of attitude of pepper growers towards improved agricultural practices in pepper. The variables, namely, scientific orientation, market orientation, educational status, risk orientation, innovativeness, social participation and age had jointly explained 67 per cent variation in the attitude of pepper growers towards improved agricultural practices in pepper. Scientific orientation alone contributed 41 per cent of variation in prediction. Education was found as the most important variable in the prediction of adoption of improved agricultural practices in pepper. This variable alone contributed 42 per cent of variation in prediction. Fifty nine per cent of variation was explained by the seven variables, namely, education, contact with extension agency, social participation, information source used, innovativeness, scientific orientation and market orientation. The pepper growers perceived the following as the major constraints in adoption of improved agricultural practices in the descending order of magnitude, extensive prevalence of pests and diseases, high cost of production inputs, lack of awareness of improved agricultural practices in pepper, traditional systems of cultivation, inadequate extension support, lack of sufficient good quality planting materials, inadequate research support, long duration of rainless period, fluctuating prices of black pepper, non-availability of literature on improved agricultural practices, non-availability of input materials and small and marginal size of holdings. The following were the solutions suggested to overcome important constraints in adoption of improved agricultural practices by pepper growers: Develop low cost technologies for the control of pests and diseases. Develop disease and drought tolerant varieties. Production and distribution of good quality planting materials. Adequate training to farmers about improved agricultural practices. Implementation of soil and moisture conservation measures. Proper marketing network coupled with remunerative price of black pepper. Supply of newer high yielding varieties to farmers.